A Sociological Investigation About the Stress and Family Adjustment Among Parents of Intellectual Developmental Disability Students - Faiza Ramzan; Abdul Waheed (SADIQ Journal of Pakistan Studies, 2023)
The study was designed to collect the information necessary to understand the families of children with Intellectual developmental disability. It was descriptive research for data collection researcher used questionnaire as a tool. The population of the present study was the parents of intellectual developmental disability (IDD) children from the special schools in Bahawalpur City. A sample of 50 parents was selected from different socio-economics status and educational background in Bahawalpur city. Parents were suitably available. The parents were seeing after the children with intellectual developmental disability (IDD) of different severity levels. Data was collected by using questionnaire and analyzed in SPSS. Major findings revealed that majority of parents were satisfied with their current life.